Multi-informant measurement of social anxiety symptoms in youth with social anxiety with and without autism - Coffman, Marika C.; Antezana, Ligia; Brown, Casper; Brown-Venegas, Amber; Richey, John A. (Frontiers in Psychiatry, 2025)
IntroductionDiscrepancies between caregiver and youth report of social anxiety symptoms persist, yet measuring social anxiety symptoms, particularly among autistic youths, is critical clinically to inform intervention planning and make correct diagnostic decisions.MethodsAccordingly, we sought to evaluate caregiver–adolescent agreement on measures of social anxiety across three diagnostic groups: (1) autistic, socially anxious adolescents (n=20), socially anxious, non-autistic adolescents (n=20), and a comparison group of non-autistic, non-socially anxious adolescents (n=20). Caregivers and adolescents completed the Anxiety Disorders Interview Schedule (ADIS), Social Anxiety module, and caregivers completed a battery of questionnaires to measure adolescent behavioral functioning in terms of adaptive, externalizing, and autism-related behaviors.ResultsCompared with adolescents, caregivers generally indicated greater observed behavioral interference (e.g., avoiding preferred activities) on the ADIS due to social anxiety symptoms (F(1, 56) = 8.48, p < 0.01). Moreover, caregivers in the autistic group reported the highest level of behavioral interference, followed by the social anxiety group, and then the comparison group. Autistic adolescents and their caregivers had the poorest agreement for social anxiety symptoms compared with the other two groups.DiscussionThese results demonstrate the differential impact of autism on the perception of social anxiety symptoms for caregivers and autistic adolescents. These results have implications for measuring social anxiety symptoms in autistic adolescents for research and clinical purposes as well as for intervention planning in this population.